1995
DOI: 10.7326/0003-4819-122-9-199505010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the Nosocomial Transmission of Tuberculosis

Abstract: Infection control measures effectively prevented nosocomial transmission of tuberculosis to health care workers. Administrative controls appear to be the most important component of a tuberculosis infection control program and should be the first focus of such a program, especially at public hospitals, where resources are most likely to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 0 publications
2
71
0
2
Order By: Relevance
“…(22) Blumberg et al studied the effectiveness of introducing such measures in a hospital in Atlanta, Georgia (USA) and reported a decrease in the number of new cases among individuals exposed to the disease and in the number of positive PPD tests among health care professionals. (29) The authors also suggested that changes in administrative policies played the most important role in achieving success, indicating that these should be the first modifications implemented in such an attempt to improve control measures.…”
Section: Discussionmentioning
confidence: 99%
“…(22) Blumberg et al studied the effectiveness of introducing such measures in a hospital in Atlanta, Georgia (USA) and reported a decrease in the number of new cases among individuals exposed to the disease and in the number of positive PPD tests among health care professionals. (29) The authors also suggested that changes in administrative policies played the most important role in achieving success, indicating that these should be the first modifications implemented in such an attempt to improve control measures.…”
Section: Discussionmentioning
confidence: 99%
“…This hierarchy of control measures has been effective in terminating outbreaks of tuberculosis and preventing nosocomial transmission (25,97). These guidelines buttressed the nation's tuberculosis control programs, which decreased M. tuberculosis rates to 3.2% in 2004, the lowest case rate since reporting began in 1953.…”
Section: Mycobacterial Pathogensmentioning
confidence: 99%
“…These outbreaks stimulated substantial investment in administrative, personal and engineering infections control measures. [5][6][7][8] Tuberculosis was popularly known as consumption for a long time. Scientifically know it as an infection caused by M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%